Growth and characterization studies of 3-aminobenzene sulfonic acid single crystal for thermal application. Issue 7 (3rd July 2022) - Gayathiridevi, K.; Pasupathi, G.; Deepa, B.; Kaviyarasu, K.; Ayeshamariam, A.
Abstract: We report the growth and characterization of 3-Amino benzene sulfonic acid (3-ABSA) of an organic single crystal for the first time under slow evaporation technique. The presence of characteristics vibrational groups and molecular structure were established by Fourier transform infrared (FTIR) and nuclear magnetic resonance (NMR) studies. The lower ultraviolet ray absorption edge was found to be 220 nm with a broad transmission window was observed in the visible region. The mechanical strength of grown crystal was assessed, and it belongs to soft material category. However, high thermal stability and other thermodynamic parameters were calculated using thermogravimetric (TGA) and differential thermal analyses (DTA). Therefore, the dielectric behavior of grown crystal was measured at various frequencies and temperature. The Kurtz powder second harmonic generation displays the second harmonic generation behavior of material and its efficiency is 0.55 times that of KDP were discussed in detail.